1976
DOI: 10.1117/12.954782
|View full text |Cite
|
Sign up to set email alerts
|

<title>Astronomical Applications Of Charge Injection Devices</title>

Abstract: During the past year several types of silicon self-scanning arrays have become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…35,36 The scientific applications of CCDs were first demonstrated in astronomy research in 1976. 37 However, a chemical application was first demonstrated by the CCDs' utility in a spectroscopic measurement; Ratzlaff and Paul employed a linear CCD for molecular absorption in 1979. 38 They showed that the CCD-produced signals are linear with both intensity and integration time in the visible region.…”
Section: Ccd and Cmos Implementation In Chemistrymentioning
confidence: 99%
“…35,36 The scientific applications of CCDs were first demonstrated in astronomy research in 1976. 37 However, a chemical application was first demonstrated by the CCDs' utility in a spectroscopic measurement; Ratzlaff and Paul employed a linear CCD for molecular absorption in 1979. 38 They showed that the CCD-produced signals are linear with both intensity and integration time in the visible region.…”
Section: Ccd and Cmos Implementation In Chemistrymentioning
confidence: 99%
“…The evaluation was carried out under low background and low temperature conditions, keeping in mind the ultimate goal of astronomical use. 2. Description of the CID array.…”
mentioning
confidence: 99%
“…By use of the row and column scanners, one can select a pixel and by applying appropriate voltages to the lines, one can either transfer the charges back and forth between the two plates of that pixel or collapse the potential well, thus injecting the charges into the substrate and creating on the plates a voltage change that can be sensed by a preamplifier. The reader interested in a more detailed explanation is referred to [1] and [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation